MARRIAGE LAW IN THE ISLAMIC WORLD: A COMPARATIVE STUDY OF INDONESIA AND SAUDI ARABIA - Azhar Nur Mawaddah Gulo; Sukiati Sukiati; Iwan Iwan (Al-Muqaranah : Jurnal Perbandingan Hukum dan Mazhab, 2026)
Marriage in Islam is an act of worship aimed at building a harmonious family based on the theological values of sakinah (love), mawaddah (love), and rahmah (mercy). However, the implementation of marriage law in various Muslim countries has a diverse knowledge base or epistemology. This study aims to examine in depth the differences in the epistemology of marriage law between Indonesia and Saudi Arabia, and their impact on the protection of domestic rights. Using a qualitative approach in normative-theoretical library research, this study dissects secondary data in the form of regulations in Indonesia and legal practices in Saudi Arabia. The research shows that Indonesia implements a positive codified legal system through Law No. 1 of 1974, the Compilation of Islamic Law (KHI), and Law No. 16 of 2019, which provides legal certainty through strengthening administration such as marriage registration and tightening requirements for polygamy. In contrast, Saudi Arabia implements an unwritten legal system (uncodified law) rooted in the methodology of the Hambali School, where legal practice relies heavily on the ijtihad of judges and fatwas of religious authorities. This difference has implications for legal protection policies, such as the strict minimum age limit for marriage in Indonesia (19 years), in contrast to Saudi Arabia, which does not set a rigid legal age limit and still recognizes men's unilateral rights in divorce.